Beneficial Effects of Statins on Seizures Independent of Their Lipid-Lowering Effect: A Narrative Review - Arash Amanlou; Ehsan Nassireslami; Ahmad Reza Dehpour; Amir Rashidian; Mohsen Chamanara (Iranian Journal of Medical Sciences, 2023)
Among the many types of central nervous system (CNS) disorders, seizures and epilepsy severely affect the quality of life and routine daily activity of the sufferers. We aimed to review research studies that investigated the effect of statins on the prevention and treatment of seizures and epilepsy. Both animal models and human studies were included in this review. This article starts with a brief introduction about seizure, its prevalence, treatment, and various animal models of seizures and epilepsy. Next, we discuss statin’s mechanism of action, side effects, and effects on neurological disorders with a specific focus on seizures. Finally, the effects of different types of statins on seizures are compared. The present review gives a better understanding of the therapeutic effects of statins on neurological disorders in animal models and human studies. This permits researchers to set up study designs to resolve current ambiguities and contradictions on the beneficial effects of statins on neurological disorders.